How do we know when social innovation works? A review and contingencymodel of social impact assessment - Molecke, Greg; Pache, Anne-Claire (Handbook of Inclusive Innovation, 2019)
Social innovations bring about novel ways to address societal challenges and ultimately aim at creating social impact by improving the condition of individuals, communities, and the planet. We define “social impact” as improvements in wellbeing, quality of life, life satisfaction, or living standards or, in an inverse view, reductions in social needs or hindrances that deprive one of the capability to live a good life. Assessing the extent of the social impact created by a given social innovation is essential to assess the relevance and the efficiency of the social innovation, to monitor it, and, ultimately, replicate and diffuse it. Yet assessing social impact is a complex process. This chapter maps the current knowledge on social impact assessment to allow researchers and innovators alike to make sense of the multiplicity of approaches currently available and to overcome the challenges associated with their implementations, particularly when it comes to promote inclusion of the most disenfranchised. The authors review the main approaches to assessing social impact and discuss the challenges associated with social impact assessment. Building upon this analysis, they propose a model that relates stages and needs in the innovation cycle with relevant social impact assessment approaches. They finally discuss future research directions that could help social impact assessment better drive social innovation and impact.